Where is the Grand Canyon? - O'Connor, Jim (Grosset & Dunlap, an imprint of Penguin Group (USA) LLC : Scholastic Inc, 2015)
Looks at the Grand Canyon, one of the Seven Natural Wonders of the World, including how it formed, which early native people lived there, and what varied wildlife can be found there now.